POTENSI TANAMAN MAKROHIDROFITA DAN SEMIHIDROFITA UNTUK REMEDIASI LIMBAH CAIR PABRIK TAPIOKA - Eko Rini Indriyatie (Universitas Tribhuwana Tunggadewi, 2007)
Potensial role of a macrohydrophyte plant (Veyivera zizanioides) and four semihydrophyte plants (Ipomoea aquatica, Cyperus iria, Commelina nudiflora, Oryza sativa) as remediators of liquid waste of tapioca industry was tested in a glasshouse for 35 days under conditions that resemble to wet and polyculture systems. Results dhowed that all type of plants grew normally on media containing tapioca liquid waste. Total biomass of Ipomoea aquatica and polyculture grown in wet conditions were 32,35 g and 38,44 g, respectively. This were higher than those of control (30,53 g and 36,39 g). Those of V. zizanioides, Cyperus iria, Commelina nudiflora and Oryza sativa were inversely observed. Hawever, V. zizanioides showed the highest tollerance index value (120,99%) compared to that of Ipomoea aquatica (91,21 %), Cyperus iria (56,62 %), Commelina nudiflora (89,63 %), Oryza sativa (83,13 %), and polyculture (62,25 %)